Indeks Kesesuaian Wisata dan Daya Dukung Ekowisata Pantai Pasir Putih di Kota Manokwari Papua Barat - Sahirudin Sahirudin; Wahyudi wahyudi; Paulus Boli (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
Pasir Putih is popular beach and favorable destination for local and domestic tourists in Manokwari. Since becoming the capital city of Papua Barat province in 2000, numbers of tourists have grown significantly. However, tourist suitability index and real carrying capacity as well as physical carrying capacity of this area were not determined yet. This research is designed to determine tourist suitability index, examine sea water quality, determine physical carrying capacity of area, real carrying capacity, and to investigate the tourist perception on management and nature for future development and promotion. Survey and questionare were used to collect the data and analysed using Microsoft excel and presented in Figures and Tables. The results indicate that Pasir Putih beach has a tourist suitability index of 90% for highly suitable. Sea water qualities are in fufillment to the Ministry of Environment and Forestry Regulation, 51/MENKLH/2004 for standard for sea water quality for beach tourism activity. The real carrying capacity for Pasir Putih beach is 626 visitor per day and physical carrying capacity of area is 1.486 visitors, which can be divided into five tourism activity of beach recreation, beach sport, swimming, snorkeling, and boat cycling. Beach swimming is the most favorable activity (44%). In addition, major tourists (54%) have a great experience with the highest satisfaction, but the majority (67%) demanding for improving public facilities.